PENGARUH LATIHAN STROKES SMASH DAN LATIHAN DRILLS SMASH TERHADAP KETEPATAN JUMPING SMASH DIPERSATUAN BULUTANGKIS BUNGO SPORT - Saputra, Deddy Rahmat; Mori Saputra, Deka Ismi; Zahra, Jumiya Ginti (Jurnal Muara Olahraga, 2023)
Abstract This research aims to find out whether there is an effect of stroke smash and drill smash training on the accuracy of jumping smash shots. This research is experimental research with a quantitative approach. The population in the study were all players at the Bungo Sport Badminton Association, totaling 20 people. The sampling technique is purposive sampling. The sample in this study was 12 U 12-17 players. The results of this research show that (1) the first hypothesis states that there is an influence of smash stroke training on jumping smash accuracy at the Bungo Sport Association, with a value of t = 6.708 while t table = 2.570 with a significance level of 0.05. These results show that tcount is greater than ttable. Soha is accepted and ho is rejected. (2) the second hypothesis which states that there is an influence of drills smash training on the accuracy of jumping smashes at the Bungo Sport Association, with a value of t = 6325 while t table = 2.570 with a significance level of 0.05. These results show that tcount is greater than ttable. Soha is accepted and ho is rejected. (3) the third hypothesis which states that there is a difference between stroke smash training and drill smash training on jumping smash accuracy at the Bungo Sport Association, with a value of t = 0.000 while t table = 2.228 with a significance level of 0.05. These results show that tcount is smaller than ttable. Soha is rejected and ho is accepted, meaning there is no difference between the two exercises. Keywords: practice smash strokes, drill smash, jumping smash, badminton